Risk assessment of lead, cadmium and copper among workshop car spray painter in Kota Bharu, Kelantan. - Ismail, Siti Fazhilah (Universiti Sains Malaysia, 2016)
Exposure to chemical hazardous at car spray workshop will lead painter to be exposed to lead, cadmium and copper. Such exposure can cause adverse health effects to car painters due to neglect of regulation and guidance of safety and health. This study was aimed to assess the risk level of lead, cadmium and copper among car paint worker in Kota Bharu. 13 subjects for exposed group and non-exposed were selected from spray painter at car and in Campus Universiti Sains Malaysia (USM) respectively .Urine samples were collected at the post-shift work for both exposed group and for nonexposed group. They were asked to answer questionnaire related to their work. Urine sample of exposed and non-exposed group were digested with Nitric Acid (HNO3), Hydrochloric Acid (HCI) and Hydrogen Peroxide (H2O2) and lead, cadmium and copper were analyzed by using the Atomic Absorption Spectrometer (AAS)-Perkin Elmer Analyst 800 to measure the level of concentration. Factors socio-demographic such as smoking, duration of exposure to chemicals, duration of employment, and intake of seafood and alcohol can cause presence of lead, cadmium and copper present in urine. In conclusion, lead, cadmium and copper concentration levels in urine can detect the presence of lead, cadmium and copper among exposed and non-exposed groups.